A MOBILE LEARNING APPLICATION TO FOSTER SUSTAINABLE AGRICULTURE THROUGH HYDROPONICS: DEVELOPMENT AND USABILITY TESTING - Siti Mahfuzah Sarif; Rozana Samah; Shri Dewi Applanaidu, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This study explores the development and usability testing of a mobile learning application tailored to provide an engaging educational experience in hydroponics for school children aged 12 years and below. The challenges faced by the agricultural education sector in capturing the interest and participation of the younger generation, where conventional methods have often struggled to engage and inspire. Embracing the principles of design thinking, this research seeks to bridge the gap in agriculture education, addressing the unique needs and preferences of younger learners in the digital age. A mobile learning application was developed, designed to combine the principles of hydroponics with interactive digital learning experiences. The design thinking methodology guided the iterative development process, placing a strong emphasis on user-centred design. The usability of the mobile learning application was assessed using the Post-Study System Usability Questionnaire (PSSUQ). Results of the usability testing revealed high levels of usability and user satisfaction among participants. The application's usefulness, user-friendly interface, engaging content, that aligned with educational objectives were among the factors contributing to its positive reception. The mobile learning application serves as a promising solution to enhance agriculture education, making hydroponics an accessible and engaging subject for school children. As a result, this research contributes to the broader goal of fostering sustainable agriculture and environmental consciousness among future generations.